The Role of Religious Scholars and Intellectuals in Reducing Migration from Afghanistan (Salam International Academic Journal, 2025)
It is a bitter yet undeniable reality that the painful history of Afghan migration abroad, which began nearly half a century ago, not only persists with the same intensity but has, in fact, increased over time. The factors and motivations driving Afghans to migrate, particularly to the United States and Europe, are diverse. The most significant of these include war and insecurity, internal conflicts and tensions, and the aspiration for a relatively peaceful and comfortable life.In light of the various and widespread harms caused by migration, which have even affected universities and academic institutions, Salam University has taken the initiative to organize a national conference. This initiative aims to highlight the negative consequences of migration and to explore strategies for its prevention. The university itself, following the emergence of the Islamic Emirate, has been affected by migration and has lost several of its professors, academic staff members, and a large number of students.There is no doubt that national authorities and decision-makers, especially religious scholars, intellectuals, and academics, bear both national and religious responsibilities. They must actively engage using rational and effective methods that can reshape the mindset of those inclined to migrate, in order to prevent further migration which ultimately harms Afghans and their homeland.In this brief and focused paper, I have attempted to draw the attention of scholars and intellectuals to their religious and national duties and to highlight their potential role in preventing or reducing the migration trend.
Keywords: Migration; Scholars; Intellectuals; Afghanistan; National Responsibility; Religious Duty